Antimicrobial Resistance and Molecular Characterization of Staphylococcus aureus Causing Childhood Pneumonia in Shanghai - Song, Zhen; Gu, Fei-Fei; Guo, Xiao-Kui; Ni, Yu-Xing; He, Ping; Han, Li-Zhong (Frontiers in Microbiology, 2017)
Staphylococcus aureus or methicillin-resistant Staphylococcus aureus (MRSA) is a major pathogen causing pneumonia among children. To estimate the prevalence and molecular properties of S. aureus in children pneumonia in Shanghai, China, One hundred and seven hospitalized children with S. aureus pneumonia from two children’s hospitals from January 2014 through June 2015 were studied. S. aureus isolates from the respiratory specimens were characterized by antimicrobial susceptibility, agr typing, toxin genes, multilocus sequence typing (MLST), spa and SCCmec typing. Fifty-eight (54.2%, 58/107) were MSSA (methicillin-susceptible Staphylococcus aureus) and 49 (45.8%, 49/107) were MRSA. No isolates were found resistant to teicoplanin, sulfamethoxazole/trimethoprim, rifampicin, quinupristin/dalfopristin, linezolid, or vancomycin. However，these isolates showed high resistant rates to erythromycin, fosfomycin-trometamol and clindamycin. The agrⅠ (87/107, 81.3%) was the most common agr allele, followed by agrⅢ(10/107, 9.3%), agrⅡ(9/107, 8.4%) and agrⅣ(1/107, 0.9%). Six pvl-positive isolates (3 MRSA and 3 MSSA) and 7 isolates of livestock associated clone ST398 (4 MRSA, 3 MSSA) were identified. CC59 was found in 35 isolates (33 MRSA and 2 MSSA), constituting majority of MRSA (33/49, 67.35%). The dominant CC were CC59 (32.7%), CC188 (13.1%), CC7 (12.1%) and CC398 (9.3%) while t172 (16.8%), t189 (12.1%), t437 (9.3%) and t091 (9.3%) were the most common spa types. In conclusion, more particular concern should appeal to ST59-SCCmecIV-t172/t437 as it is the most common epidemic clone causing pneumonia among children in Shanghai.